The new candidate IPV6 address size prediction - Batiha, Khaldoun (Journal of Advanced Computer Science & Technology, 2014)
IPv4 protocol is now no more sufficient due to its limited address space where this protocol uses only 32-bit for addressing. IPv6 protocol is the next protocol which was introduced as a new protocol that provide a huge address space .In This paper we discussed the significant overhead in the IPv6 standard packet due to its 128 bits address size, so we develop three different studies in order to generate a prediction of exhibition date for several address sizes so we can suggest another size for address size in IPv6 to improve the overall performance of the internet and tolerate the overhead by reducing the address size. In the same time this size should accommodate the accelerated growth in needs for unassigned blocks of addresses for very long time. Keywords: Ipv4 Protocol, Ipv6 Protocol, Addressing Types, Ipv6 Header, Exhibition Date, Address Pool.